Lung ultrasound compared with bedside chest radiography in a paediatric cardiac intensive care unit. (15th October 2020) - Hasan, Tammam; Bonetti, Simone; Gioachin, Anna; Bulgarelli, Ambra; Bartolacelli, Ylenia; Ragni, Luca; Gargiulo, Gaetano D.; Donti, Andrea
Abstract: Aim: Postoperative recovery of children with heart disease is encumbered by pulmonary complications like pneumothorax (PNX), pleural effusion (PLE), interstitial oedema and pulmonary consolidation (PC). Recently, lung ultrasound (LUS) has become an important diagnostic tool for evaluation of pulmonary diseases in the paediatric context. LUS is accurate in diagnosing pleural and parenchymal diseases. The aim of this study was to evaluate the accuracy of LUS in the identification of PNX, PLE and PC in a paediatric population of patients with congenital heart disease after heart surgery. Methods: Fifty‐three patients aged 0‐17 years who underwent cardiac surgery were evaluated in the postoperative period by chest X‐ray (CXR) and LUS at the same time. The methods where compared for recognition of PNX, PLE and PC. Results: LUS showed a good agreement for PNX and a moderate agreement for both PLE and PC. LUS also showed a significantly superior relative sensitivity than CXR for PC and PLE and a significantly inferior relative sensitivity for PNX. Conclusion: This study confirms that LUS has a sufficient agreement rate with the current clinical standard (CXR). Non‐inferiority in diagnosis together with the easiness of bedside performance makes LUS a very attractive tool for the paediatric cardiac intensive care unit.